Effectiveness of Ultrasound-Guided Percutaneous Electrolysis for Musculoskeletal Pain: A Systematic Review and Meta-Analysis. Issue 5 (6th November 2020) - Gómez-Chiguano, Guido F; Navarro-Santana, Marcos J; Cleland, Joshua A; Arias-Buría, Jose L; Fernández-de-las-Peñas, César; Ortega-Santiago, Ricardo; Plaza-Manzano, Gustavo
Abstract: Objective: To evaluate the effects of ultrasound-guided percutaneous electrolysis alone or as an adjunct to other interventions on pain and pain-related disability for musculoskeletal pain conditions. Databases and Data Treatment: Search of MEDLINE database, Allied and Complementary Medicine Database, EMBASE database, Cumulative Index to Nursing & Allied Health Literature database, EBSCO database, PubMed database, Physiotherapy Evidence Database, Cochrane Library database, Scopus database, and Web of Science database. Randomized controlled trials in which at least one group received ultrasound-guided percutaneous electrolysis for treatment of musculoskeletal pain. To be eligible, studies had to include humans and collect outcomes on pain intensity and pain-related disability for musculoskeletal pain syndromes. Data were extracted by two reviewers. The risk of bias was assessed by the Cochrane Guidelines and the quality of evidence was reported using the Grading of Recommendations Assessment, Development and Evaluation approach. Standardized mean differences (SMDs) and random effects were calculated. Results: Ten studies were included. The meta-analysis found that ultrasound-guided percutaneous electrolysis reduced the mean pain intensity by –2.06 (95% confidence interval [CI], –2.69 to –1.42) and the pain intensity as assessed with a visual analog scale or a numeric pain rating scale with a large size effect (SMD = –1.15; 95% CI, –1.48 to –0.81) and also improved pain-related disability with a large size effect (SMD = 0.95; 95% CI, 0.73–1.18) as compared with comparison groups. No differences in effect sizes were found among the short-term, midterm, and long-term follow-ups. The risk of bias was generally low, but the heterogeneity of the overall result downgraded the evidence level. Trials included heterogeneous musculoskeletal pain conditions and short-term, midterm, and long-term follow-ups. Conclusion: Moderate evidence suggests positive effects of ultrasound-guided percutaneous electrolysis for pain and pain-related disability in musculoskeletal pain conditions relative to a comparison group in the short term, midterm, and long term.